Peran Pendidikan Keluarga dalam Pencegahan Bahaya Narkoba pada Remaja - Ati Kusmawati; Aprilia Cahyani; Layla Fitri; Zalfa Sofia Avrianti Arifin (Jurnal Hukum dan Sosial Politik, 2025)
Drug abuse among adolescents is a serious problem that requires a comprehensive prevention strategy. One key element in this effort is family education, which plays a frontline role in protecting adolescents from the negative influence of drugs. Through consistent education, supervision, and emotional support, families can build a foundation for positive behavior and mental resilience in adolescents. Effective family education includes open communication between parents and children, teaching moral and religious values, and creating a safe, harmonious, and warm home environment. Healthy communication allows adolescents to feel comfortable discussing problems or pressures they face, thereby minimizing the risk of falling into drug abuse. In addition to the role of the family, psychological approaches such as Cognitive Behavioral Therapy (CBT) have proven effective in strengthening adolescents' resilience to social pressures and the temptation of drugs. CBT focuses on helping individuals recognize and change negative thought patterns and risky behaviors that trigger abuse. With CBT techniques, adolescents can learn stress management skills, improve decision-making skills, and develop healthier, adaptive behaviors. The integration of family education and CBT therapy results in a more holistic prevention approach. Families provide a foundation of morals, values, and emotional support, while CBT strengthens adolescents' psychological abilities to face life's challenges. This synergy can increase resilience, reduce vulnerability to negative influences, and equip adolescents with effective strategies for resisting drugs. By optimizing the role of the family and combining it with psychological interventions, it is hoped that a healthy, productive young generation will emerge, free from the threat of drugs, enabling them to contribute positively to society and the future of the nation.